Penerapan Model Role Playing dalam Meningkatkan Prestasi Belajar Siswa Materi Sistem Pencernaan pada Manusia - Ariani, Nurhofifah; Hasbiyati, Haning; Nurjanah, Umi (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
The role of biology learning is very important as an effort to improve student learning activities and outcomes. This study aims to determine an increase in student learning activities and outcomes in MTs Ma'arif Ambulu after using the Discovery Learning learning model. This type of research is a classroom action research (CAR) with 2 cycles where one cycle consists of four steps namely planning, action, observation, and reflection. The results of the first cycle test that was carried out obtained a percentage of 68.75% and the average activity of cycle I students was 60.6% while the results of the second cycle test were 87.5% and the average activity of cycle II students was 92.5%. This shows that the ability of activities and student learning outcomes have increased with the application of discovery learning models.